If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x/3+x=-(x-2)
We move all terms to the left:
2x/3+x-(-(x-2))=0
We add all the numbers together, and all the variables
x+2x/3-(-(x-2))=0
We multiply all the terms by the denominator
x*3+2x-((-(x-2)))*3=0
We add all the numbers together, and all the variables
2x+x*3-((-(x-2)))*3=0
Wy multiply elements
2x+3x-((-(x-2)))*3=0
We add all the numbers together, and all the variables
5x-((-(x-2)))*3=0
| b=9b=20 | | 5b+8=A | | 5s-4s=12 | | 14y-9y=5 | | x^2+x-39=0 | | 14y-9y=12 | | x−6=−4 | | 6k-2k=20k | | x+7/14=-1-2/3x | | x+7=-12/3x | | |-2x|=9x+18 | | 5+4=3x+1 | | -2x=9x+8 | | -2x+6=5x-13 | | 7n17=39 | | 44x+9=97 | | 13+2x=3x-11 | | 17-2x=31=3x | | 28x^2-23x+15=0 | | x=123*5/2+6112 | | v=5×3×3 | | 2^n-1=1024 | | 28x^2=-23x+15 | | 1,8x=270 | | 2x+3,5=2,8 | | 5h+10=180 | | 3a-30=90 | | 3x8=2× | | 9d=4d+30 | | 3(x+2)=-5(x-2) | | 2y+45=90 | | x/6+2=x/3 |